Evaluation of Oxidation Stability of Organic and Conventional Hazelnut Oils - Caner Ümit Topçu; Sümeyye Şahin (Journal of Agricultural Sciences)
In this study, the oxidation stabilities of organic hazelnut oils (OHO) were compared to conventional hazelnut oils (CHO). For this purpose, oxidation parameters such as peroxide value (PV), free fatty acid (FFA), anisidine value (AV), volatile lipid oxidation compounds (VLOC), fatty acid composition, and total antioxidant capacity (TAC) of the hazelnut oil samples were investigated under conditions of accelerated storage. At the beginning of storage, OHO had lower PV, higher AV, TAC and linoleic acid content than CHO and similar FFA, VLOC, palmitic, stearic, and oleic acids contents to CHO. As expected, PV, FFA and AV increased in OHO and CHO during storage, while TAC decreased. No significant difference between OHO and CHO was observed in terms of FFA, TAC, palmitic and stearic acid contents at the accelerated storage condition. When compared to CHO, OHO showed lower oleic acid and higher linoleic acid at the end of storage. During storage, the highest AV and PV were determined in OHO. Results reveal that OHO has lower oxidation stability than CHO. According to these results, it can be recommended to consume the OHO without being exposed to long-term oxidation.